Affordable housing in Saudi Arabia's vision 2030: new developments and new challenges. Issue 1 (12th June 2020) - Alqahtany, Ali
Abstract : Purpose: The purpose of this paper is to discuss the housing delivery within the Saudi Vision 2030 through an in-depth reading of the Saudi Vision 2030 from the researcher's point of view and to identify the most significant aspects that may affect housing delivery in the country. Design/methodology/approach: In this study, the desktop study technique was followed to review the key related literature, collect the data and analyze secondary data. The content analysis technique was used for data analysis of gathered documents and secondary data. Findings: The findings reveal that there are several commitments in the Saudi Vision 2030 from the Saudi Government to be an exemplary leading nation in all aspects, including the delivery of affordable housing. Housing shortage, housing cost, demographic changes and land scarcity are identified as significant reasons for the lack of providing affordable housing. Research limitations/implications: The opinions of policymakers is very important, but due to time limitation, it has not been addressed. Future research can assess the Saudi Vision 2030 based on the study of the policymakers, professionals and academics to have better insights. Originality/value: The paper contributes to discussing the housing delivery within the Saudi Vision 2030 and identifying the most significant aspects that may affect the housing delivery from the researcher's point of view. Only a few studies have discussed the housing issues within the Saudi Vision 2030.